Power Sector Scenario for Rural Electrification of Bhutan - Lhazom, Kezang; Thanarak, Prapita (วารสารวิชาการ มหาวิทยาลัยราชภัฏอุตรดิตถ์, 2019)
Bhutan’s electricity access rate has increased from 61 percent in 2006 to 100 percent in 2016, ahead of the country’s initial 2020 goal. On-grid hydropower is Bhutan’s main energy source and the main driver behind its rapid expansion of electricity access. The country’s mountainous terrain makes grid extension difficult in the remote rural areas where around 4,000 households are located. As a result, the government has made off-grid renewable energy projects a significant development effort under the nation’s five-year plans, providing around 2,000 rural households with solar home systems and repairing an additional 1,000. Similar donor-assisted grant projects have filled the rest of the country’s electricity gap. Although the government of Bhutan achieved the remarkable feat of 100 percent electricity access, it lacks the resources and workforce to sustain these projects on its own. The country’s mountainous terrain makes remote areas difficult for government workers to access. Communities will ultimately need the training to install and repair systems themselves, a strategy that would also lead to more jobs in remote, off-grid areas. A few pilot community-based projects exist, but Bhutan’s remote rural areas need more.